Philippines : Country Procurement Assessment Report, Second Update - World Bank (Washington, DC, 2012)
The Country Procurement Assessment Report (CPAR) Second Update report was prepared in November 2004. This report is a follow-up of the original CPAR, which was part of the Public Expenditures, Procurement and Financial Management Review, and the CPAR Update which was published in February 2004. The original CPAR was prepared in June 2002 and published in March 2003. The paper includes the following headings: foreword; introduction; big achievements so far; assessment of progress; consolidated agreed actions; procurement under Foreign Assisted Projects (FAPs); and funding requirement for agreed actions.